RHAMM Expression in the Rat Endometrium during the Estrous Cycle and following Implantation - K Ozbilgin; B Boz; K Tuğyan; S Inan; S Vatansever (JRI, 2012)
Background: Receptor for hyaluronic acid mediated motility (RHAMM) has intracellular and extracellular functions. In this study, we focus on the expression of RHAMM in the rat uterus during estrous cycle and implantation period. Methods: The female adult rats were divided into six groups following estrous cycle determination (n=36). The utreri of rats were collected according to estrous cycle phases (menstruation group). For the implantation groups, uteri were obtained on D4, D5 and D6 (day of implantation) of pregnancy. The tissue samples were fixed and cut into 5 µm thick sections. RHAMM was investigated using immunohistochemical techniques and the intensity of RHAMM was evaluated by using the Hscore technique. Comparisons between groups were performed using Kruskal-Wallis test. Results: The RHAMM immunoreactivity of uterine antimesometrial epithelium (343.00±12.81), mesometrial subepithelium (285.00±27.26) and mesometrial stroma (270.00±36.00) were more prominent (p<0.05) in the proestrus than estrus (275.00± 25.96; 220.00±14.48; 218.00±11.19) and diestrus (262.00±20.71; 192.50± 29.25; 216.00±12.97) groups, respectively. The most intense staining was seen in the epithelium on day four (275.50±30.06) and six (293.50±34.47) of pregnancy (p<0.05). Strong RHAMM expressions were in both mature and predecidual cells on D5 (256.00±18.71), (247.50±22.14) and D6 (256.00±30.72), (265.00±14.87), respectively. RHAMM expression was prominent in the nondecidual region on D5 (270.00± 13.36). Conclusion: Considering the role of RHAMM in cell proliferation, differentiation and angiogenesis, spatiotemporal expression of RHAMM in the uterus during estrous cycle and peri-implantation period is a means through which uterus becomes receptive for developing an embryo.
Keywords: Estrous cycle, Immunohistochemistry, Implantation, RHAMM, Uterus